0323 Gender-Specific Differences in Self-Reported Factors Attributed to Sleep Disruption. (25th May 2022) - Ruder, Michael; Gahan, Luke; Raymann, Roy; Watson, Nathaniel; Gottlieb, Elie
Abstract: Introduction: Women are more likely to report sleep difficulties. There are many ways for sleep to be disrupted (social influences, external sensory stimuli, somatic cues) but limited data exists on the relative burden of these disruptors. The purpose of the present analysis was to compare the occurrence of disruptors between males and females of equal ages. Methods: We used self-reported data from the PSG-validated SleepScore mobile app to analyze the relative occurrence of a variety of sleep disruptors in an age- and gender-balanced sample of users (39, 560 male and 39, 560 female, median age=41, SD=15). Fisher's exact test was used to examine whether gender was a significant factor in the likelihood of reporting each disruptor. Disruptors were categorized as follows: somatic cues included hot flashes/thermal discomfort, chronic pain, bathroom visits, and heartburn; external sensory stimuli included temperature, light, and noise; social influences included: bed partner, pet, and children. All p < 0.00001 results are reported. Results: Women were significantly more likely than males to report at least one sleep disruptor (Odds ratio (OR): 2.29, prevalence: 90% vs 80%) and were more likely to report sleep disruption attributed to external stimuli (OR: 1.61, prevalence: 54% vs 42%), somatic cues (OR: 1.66, prevalence: 68% vs 56%), and social influences (OR: 1.95, prevalence: 50% vs 34%). Among somatic cues, women were more likely than males to report hot flashes/thermal discomfort (OR: 3.42), chronic pain (OR: 2.32), bathroom visits (OR: 1.24), and heartburn (OR: 1.14). Among external sensory stimuli, women were more likely than males to report sleep disruption attributed to sound (OR: 1.58), light (OR: 1.54), and temperature (OR: 1.54). Among social influences related disruptive factors, women were more likely than males to report sleep disruption attributed to pets (OR: 2.31), bed partners (OR: 1.65), and children (OR: 1.62). Conclusion: The present analysis found that women reported higher rates of regular disruption for every cause. These findings highlight the role of gender in sleep-health reporting behavior and mirror other findings showing lower symptom reporting and healthcare utilization among males. Support (If Any):